A-143 Sorry, I Wasn't Paying Attention. The Moderating Role of Auditory Attention on the Relationship between Age and Verbal Learning. (30th August 2021) - Laique, Aamir; Khan, Humza; Hizel, Loren P; Breting, Leslie Guidotti; Geary, Elizabeth; Sweet, Jerry J
Abstract: Objective: Attentional difficulties are known to negatively impact learning (Hervey et al., 2004; Alderson et al., 2013). This study builds upon previous work examining the effect of sustained visual attention as a moderator of age and learning (Thomas et al., 2019) by examining performance on an auditory attention measure as a moderator of the relationship between age and performance on a verbal list-learning task. Method: Archival data from 424 adults (Mage = 36.01, SD = 15.13) were collected at an outpatient clinic. Auditory attention was assessed via the Brief Test of Attention (BTA) raw score. Learning was assessed via the California Verbal Learning Test (CVLT-II) total T-Score (Trials 1–5). Results: Results of a hierarchical linear regression indicated a significant effect between BTA and learning, (β = 0.287, F(1, 422) = 17.993, p < 0.001, ΔR2 = 0.078). There was no significant effect between age and learning, (β = 0.022, F(1, 422) = 0.204, p = 0.652, ΔR2 = 0.000). Additional results from a simple moderated regression analysis indicated a significant overall model between age, learning and BTA (F(3, 420) = 15.749, p < 0.001, ΔR2 = 0.1011) with BTA having a significant positive interaction effect on the relation between age and learning (β = 0.816, F(1, 420) = 10.436, p = < 0.001, ΔR2 = 0.022). Conclusion: Sustained attention has been shown to be an important consideration when assessing verbal learning and memory performance. Present results demonstrate that when accounting for age, auditory attention is a significant positive predictor of performance on measures of verbal learning. Additionally, confirming prior research, performances on auditory attention and verbal learning measures are positively correlated.